The status and roles of the 406th Medical General Laboratory of the U.S. Army, 1946-1953 - Taewoo KIM (Uisahak, 2022)
In 1946, the U.S. Army established the 406th Medical General Laboratory as the central medical research institute for their new Asia-Pacific-occupied area. The primary mission of the 406th medical laboratory was to supplement the epidemiologic, sanitary, and diagnostic services available in other medical facilities and hospitals, and to investigate outbreaks of disease and conditions which affect or may affect the health of the people in the occupied area. At the time of its establishment, the 406th laboratory had considerable difficulties securing researchers, but it solved the related problems by actively cooperating with Japanese medical researchers and research institutes. According to the statistics in 1947, the 406th laboratory consisted of 46% of its total research personnel, Japanese researchers. The 406th medical laboratory’s professional research departments included the department of Pathology, Serology, Bacteriology, Medical Zoology, Chemistry, Virus and Ricketts, Entomology (established in 1949), and Epidemiology (established in 1951). All research departments played a central role in the Asia-Pacific region in their professional fields. For example, the department of Pathology functioned as the “histopathology center of all hospitals in Japan, Korea, and the Mariana-Bonin Command” under the provision of “Army Regulation 40-410,” and the department of Chemistry was called an “analytical chemistry laboratory for the Far East Command” because it performed various chemical experiments for many medical facilities in the area with insufficient research facilities.